Temporal Correlation Between Urban Microclimate, Vector Mosquito Abundance, and Dengue Cases. Issue 3 (19th March 2022) - Faridah, Lia; Fauziah, Nisa; Agustian, Dwi; Mindra Jaya, I Gede Nyoman; Eka Putra, Ramadhani; Ekawardhani, Savira; Hidayath, Nurrachman; Damar Djati, Imam; Carvajal, Thaddeus M; Mayasari, Wulan; Ruluwedrata Rinawan, Fedri; Watanabe, Kozo
Abstract: Dengue Hemorrhagic Fever (DHF) is a major mosquito-borne viral disease. Studies have reported a strong correlation between weather, the abundance of Aedes aegypti, the vector of DHF virus, and dengue incidence. However, this conclusion has been based on the general climate pattern of wide regions. In general, however, the human population, level of infrastructure, and land-use change in rural and urban areas often produce localized climate patterns that may influence the interaction between climate, vector abundance, and dengue incidence. Thoroughly understanding this correlation will allow the development of a customized and precise local early warning system. To achieve this purpose, we conducted a cohort study, during January-December 2017, in 16 districts in Bandung, West Java, Indonesia. In the selected areas, local weather stations and modified light mosquito traps were set up to obtain data regarding daily weather and the abundance of adult female Ae. aegypti. A generalized linear model was applied to analyze the effect of local weather and female adult Ae. aegypti on the number of dengue cases. The result showed a significant non-linear correlation among mosquito abundance, maximum temperature, and dengue cases. Using our model, the data showed that the addition of a single adult Ae. aegypti mosquito increased the risk of dengue infection by 1.8%, while increasing the maximum temperature by one degree decreased the risk by 17%. This finding suggests specific actionable insights needed to supplement existing mosquito eradication programs.